2012
DOI: 10.1155/2012/517591
|View full text |Cite
|
Sign up to set email alerts
|

Interferometry with Vortices

Abstract: Interference of optical beams with optical vortices is often encountered in singular optics. Since interferometry makes the phase observable by intensity measurement, it brings out a host of applications and helps to understand the optical vortex. In this article we present an optical vortex interferometer that can be used in optical testing and has the potential to increase the accuracy of measurements. In an optical vortex interferometer (OVI), a lattice of vortices is formed, and the movement of the cores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 87 publications
0
23
0
2
Order By: Relevance
“…The ratio of linear to orbital light momenta forms, given in equation (2), can be interpreted in a certain geometrical sense. Light orbital angular momentum is directly proportional to linear momentum in such a way L depends on the orientation of P along of the propagation axis.…”
Section: Linearly Polarized Light Beam With Orbital Angular Momentummentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of linear to orbital light momenta forms, given in equation (2), can be interpreted in a certain geometrical sense. Light orbital angular momentum is directly proportional to linear momentum in such a way L depends on the orientation of P along of the propagation axis.…”
Section: Linearly Polarized Light Beam With Orbital Angular Momentummentioning
confidence: 99%
“…It is easy to use equations (2) and (7) to show that orbital angular momentum vanishes when the axial linear momentum is perfectly aligned with the propagation axis (φ = 0). Note that singularity point exists at the center of a vortex beam.…”
Section: Linearly Polarized Light Beam With Orbital Angular Momentummentioning
confidence: 99%
See 1 more Smart Citation
“…The topology is such that all the wavefronts which are disconnected and separated by distance k with each other in an otherwise non-singular beam, become connected thereby forming a single wavefront filling the entire space. The optical vortices can be characterized by various interferometry techniques [4][5][6][7]. In two beam interferometry, fork-type fringes (characteristic of phase singularity) appear at the singular region.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent stable beams (cSTBs), such as HG, LG, HLG, and IG modes, and coherent spiral beams (cSPBs) [16][17][18][19][20] are widely used nowadays for particle manipulation [21,22], resolution improvement in microscopy [23][24][25][26], free-space communication [27], atmosphere monitoring [28,29], etc. Moreover, it has been shown that as well as the Bessel beams, the cSTBs (and similarly, the cSPBs) are able to reconstruct their forms after propagation through small obstacles.…”
Section: Introductionmentioning
confidence: 99%